Graphogame: a possibility of exploring the game in the classroom in the initial series (Research, Society and Development, 2022)
With globalization and the change of scenario generated by technological advances, new ways of making knowledge effective have become part of the students' reality. In this sense, this article aims to present the Graphogame application as a possibility of exploring games in the classroom in the early grades. Regarding the methodology, it is a qualitative bibliographic survey with a descriptive approach, seeking to present through research, official documents and recent articles the relevance of Graphogame as a facilitating resource in the literacy process from its description. The results pointed to the effectiveness of using the application in the literacy and literacy process, proving to be a very effective tool in the educational field, both for students and teachers. Graphogame proved to be very useful, taking into account its pedagogical aspects and the establishment of dialogue with the reality in which the student lives.